Anatomia das paixões: a concepção somatopsíquica de Descartes e sua relação com a medicina - Juliana da Silveira Pinheiro (2012)
This thesis deals with the study of somatic aspects of emotions in the Descartess doctrine, which we call "Cartesian somatopsychic conception", and its connection with medicine, needed to understand the elements and functioning of the body involved in explaining the emergence of passions. Thus, we show how medical knowledge of Descartes contributed to the preparation of his "psychology". In this work, we emphasize the role of the body in understanding the passions and its genesis, so that the Cartesian "psychology" should be understood not as a metaphysical study of psykhé, but as a study of the mental events that take place in the relationship between body and soul. For this, we clarify the metaphysical dualist context in which this theory is inserted, according to which body and soul are completely different substances, as well as the notion of substantial union, by which these substances interact, forming the human compound and providing the emergence of passions. Moreover, we place the medical knowledge of Descartes against the panorama of medicine of his day which was still strongly marked by Galenic tradition - and show briefly how he acquired andbuilt it through the practice of dissection, dialogue with contemporary physicians and medical literature. Therefore, we conducted a detailed examination of the biological conditions of emotions, taking elements from anatomy and physiology, such as blood, blood circulation, theanimal spirits, the nerves, the brain, the pineal gland and physical memory. Finally, we reflect on the extent of biological explanations with regard to emotions, whereas, in the context Cartesian passions thoughts are irreducible to bodily movements. We question, therefore, the possibility of mechanization and physical determinism of the passions, showing that the physiological approach has limits imposed by substance dualism. This is the specificity of the Cartesian psychology: to link organic causes with the subjective and immaterial experience ofpassions, supporting the study of the soul in the body's physiology.